POST HYSTERECTOMY SPONTANEOUS RUPTURE OF SPLEEN - Bahli, Zahid M; Kennedy, Kathy (Journal of Ayub Medical College Abbottabad, 2009)
Spontaneous rupture of spleen is a rare entity in the world of obstetrics and gynaecology. The obstetricians-gynaecologist has to confront with ruptured spleen sometimes in their practice. Ruptured spleen is not uncommon in trauma and some surgical procedures in upper abdomen. Splenic rupture after hysterectomy is exceedingly rare occurrence. However it should be considered as part of diagnostic workup in any unstable post hysterectomy subject with high degree of suspicion along with other differential diagnosis. Early reorganisation of this potentially life-threatening complication is very important for the wellbeing of patient and carries medico legal significance as well. We are reporting fourth case of spontaneous rupture spleen after abdominal hysterectomy found in the literature along with literature review and update on the topic regarding its diagnostic criteria. Keywords: Spontaneous rupture, rupture, spleen, complications, hysterectomy, post hysterectomy